2020
DOI: 10.3390/nu12061756
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Composition of Breast Milk from Women of Different Ethnicity from the Manawatu—Wanganui Region of New Zealand

Abstract: Human breastmilk components, the microbiota and immune modulatory proteins have vital roles in infant gut and immune development. In a population of breastfeeding women (n = 78) of different ethnicities (Asian, Māori and Pacific Island, New Zealand European) and their infants living in the Manawatu–Wanganui region of New Zealand, we examined the microbiota and immune modulatory proteins in the breast milk, and the fecal microbiota of mothers and infants. Breast milk and fecal samples were collected over a one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Our study revealed no impact of maternal BMI on milk microbiome diversity. This finding was also reported across several other studies 16 , 33 , 62 . However, Cabrera-Rubio et al reported that maternal BMI and weight gain during pregnancy had an impact on bacterial composition and diversity in breast milk, with high BMI associated with a decrease in diversity.…”
Section: Discussionsupporting
confidence: 90%
“…Our study revealed no impact of maternal BMI on milk microbiome diversity. This finding was also reported across several other studies 16 , 33 , 62 . However, Cabrera-Rubio et al reported that maternal BMI and weight gain during pregnancy had an impact on bacterial composition and diversity in breast milk, with high BMI associated with a decrease in diversity.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, recent evidence has shown breastfeeding practices and milk collection methods would influence breast milk microbiota composition [ 9 ]. Results regarding the potential impact of maternal body mass index (BMI) and weight gain over pregnancy on breast milk microbiota are also still contradictory [ 13 , 14 , 15 , 16 ]. Similarly, while other studies found differences in milk microbiota according to lactation period [ 13 , 17 ] and feeding method [ 9 ], others reported a stable composition over time [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…50 There are similar findings for human milk. 51,52 Although findings are somewhat mixed, [53][54][55] there is substantial evidence that some soluble factors and characteristics (e.g., antioxidant capacity) in milk can be influenced by refrigeration and freezing, whereas others (e.g., human milk oligosaccharides) are extraordinarily stable. [56][57][58] It has been shown that prolonged storage at 4°C reduces the infectious titer of hepatitis C and Zika virus that has been spiked into milk.…”
Section: Temperature and Storagementioning
confidence: 99%